Feminism Among Muslimah Students: A Gender Perspective Study Through Islamic Values - Firzana Farah Amira; Hilman Taufiq Abdillah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to understand how Muslimah students at the Faculty of Art and Design Education UPI interpret feminism in three main dimensions: humanization in peer relations, liberation: impact on the self, and transcendence: influence on religious understanding. Methodology: A qualitative phenomenological technique was used in this investigation. In-depth interviews with Muslimah students at FPSD UPI were used to gather data, which were bolstered by document analysis and observation. The data was interpreted using thematic analysis, which concentrated on the aspects of transcendence, liberation, and humanisation within the context of Islamic principles. Main Findings: The study reveals that Muslimah students at FPSD UPI interpret feminism in diverse ways across three dimensions: humanization, liberation, and transcendence. Feminism encourages more inclusive social interactions, inspires artistic expression on gender themes, and prompts reflective engagement with religious teachings. While some view feminism as compatible with Islamic values, others experience tension, showing varied levels of internalization shaped by personal, cultural, and spiritual contexts. Novelty/Originality of this study: This study provides a fresh perspective by examining how Muslimah students in a department of art and design see feminism from an Islamic perspective. By presenting feminism in three interconnected dimensions: humanization, freedom, and transcendence, it contributes to the current conversation by emphasising the contextual interaction between gender consciousness, artistic expression, and religious knowledge in an academic context with cultural roots.